Fetal Renal Obstruction is Early Detected during Pregnancy by Ultrasonography at Urban Hospital (Naraynganj) (Medicine Today, 2017)
Over the last 3years (September 2012 to September 2015) for the period of 36 months after searching of all gravid uterus ultrasonography report only 40 patients having hydronephrosis detected during antenatal checkup both Naraynganj General Hospital Radiology and Imaging department and Private Clinic, primary finding is oligo hydraminos between 10 weeks to 16 weeks of gestation. All the patients of our study population were subjected to imaging by ultrasonography. This was a prospective study. Out of 40 fetus hydronephrosis were graded according to sonographic grading system. There were two fetus of grade 0, eight fetus of grade-1, eleven fetus grade-2, are nineteen fetus of grade 3 hydronephrosis on advance pregnancyMedicine Today 2016 Vol.28(2): 72-74